A universal‐input high‐power‐factor power supply without electrolytic capacitor for multiple lighting LED lamps. (13th November 2011) - Ma, Hongbo; Lai, Jih‐Sheng (Jason); Feng, Quanyuan; Yu, Wensong; Zheng, Cong
SUMMARY The AC–DC power supply for LED lighting application requires a long lifetime while maintaining high‐efficiency, high power factor and low cost. However, a typical design uses electrolytic capacitor as storage capacitor, which is not only bulky but also with short life span, thus hampering performance improvement of the entire LED lighting system. In this article, a SEPIC‐derived power factor correction topology is proposed as the first stage for driving multiple lighting LED lamps. Along with a relatively large voltage ripple allowable in a two‐stage design, the proposal of LED lamp driver is able to eliminate the electrolytic capacitor while maintaining high power factor and high efficiency. To further increase the efficiency of LED driver, we introduced and used the twin‐bus buck converter as the second‐stage current regulator with Pulse Width Modulation (PWM) dimming function. The basic operating principle and the deign consideration are discussed in detail. A 50‐W prototype has been built and tested to verify the proposal. Copyright © 2011 John Wiley & Sons, Ltd.